Investigation of Job Satisfaction of Nurses - Canan Eraydın; Ozlem Kardaş Kin; Sinem Andık; Uğur Türk (Association of Nurse Managers, 2021)
INTRODUCTION: This descriptive study was carried out in order to determine the job satisfaction of the nurses working in the Application and Research Hospital and the State Hospital. METHODS: The research was carried out in descriptive and cross-sectional research design. The study population consisted of 400 nurses working in the Research Hospital and the State Hospital in Zonguldak Provincial Center between May 1, 2019 and June 30, 2019. The sample of 220 nurses, aged between 18-65 years, who accepted to participate in the study, and completed at least 1 year in their positions have been evaluated using research data collection tools of 'Personal Information Form' and 'Job Satisfaction Scale'. Descriptive statistics were used for statistical analysis of continuous (quantitative) variables. Categorical variables were given as numbers, percentages, 'mean (.+- standard deviation), minimum and maximum values. Kruskal-Wallis and Mann- Whitney U tests were used to compare the means of categorical data. RESULTS: In this study, the level of job satisfaction of nurses was found to be at a medium level (86.18 +- 21.73). Mean overall Job Satisfaction Scale scores of the nurses working in a university and state hospital were found to be 89.77 +- 22.05, and 82.46 +- 20.86 points, respectively. Nurses who worked with a 24-hour shift 1-2 times or did not work with a 24-hour shift in last month had higher scores than others in subscale of business policy (p<0,05). DISCUSSION AND CONCLUSION: In this study, it was determined that the job satisfaction level of the nurses was at a medium level. In order to increase job satisfaction, it may be beneficial to make new plans to improve the weekly working hours of nurses working for 5 years or more, to take into account the requests of the nurses about the unit they will work, and to support participation in scientific activities in nursing.